The impact of long-term land leases on farm investment: Evidence from the Irish dairy sector. (March 2023) - Bradfield, Tracy; Butler, Robert; Dillon, Emma J.; Hennessy, Thia; Loughrey, Jason
Abstract: The European Union milk quota abolition in 2015 resulted in rapid dairy farm expansion across many Member States. Continued production growth requires both capital and herd investment with secure access to land resources being important for new and expanding farmers. As land sales and rental remain low in Ireland, tax incentives to encourage long-term land rental were increased in 2015. This paper assesses the influence of the length of land leases on dairy farm investment using farm-level data from 2015 to 2018 in the context of low levels of land sales and land rental, and liberal market regulations in Ireland. We find a positive association between lease lengths and both the probability and level of capital investment which is particularly important for farmers with a high portion of land rented in. We find that herd investment is not influenced by the duration of land leases. Our findings call for an extension of policies that encourage land rental on secure leases, especially for young farmers, to increase certainty and support growth in the industry. Highlights: Tax incentives are in place in Ireland to encourage the leasing out of land on long-term leases. We find a positive association between lease length and the probability and level of capital investment on dairy farms. There is a positive association between capital grants and dairy farms' level of capital investment, but age is not an influencing factor. Herd investment, which can be easily reversed, is not influenced by land lease durations. Further investment incentives for young farmers are required to support the economic sustainability of the sector.